Metabolic response to an acute bout of mild dynamic exercise performed under normobaric moderate hypoxia: A NMR-based metabolomics study - Flaminia Cesare Marincola; Daniela Masu; Veronica Libonati; Michela Tozzi; Raffaella Isola; Romina Vargiu; Elisabetta Marini; Silvana Roberto; Sara Magnani; Giovanna Ghiani; Gabriele Mulliri; Antonio Crisafulli; et al. (PLoS ONE, 2025)
The combination of hypoxia and exercise offers significant potential benefits for non-athletic individuals, particularly in clinical and rehabilitation settings. Personalized hypoxic exercise programs can be tailored to improve cardiovascular and metabolic health, enhance recovery, and promote adaptation to low-oxygen environments. However, finding the optimal balance between exercise variables (intensity, duration, frequency, type of exercise), and hypoxic exposure parameters (altitude level, duration, session frequency), remains challenging. Further research is needed to understand how these variables interact to optimize hypoxic exercise protocols. In the present study, we explored the effects of a single session of mild dynamic exercise conducted in normobaric hypoxia (FiO2 = 13.5%) on the plasma and urine metabolome of thirteen healthy young adults (age 29.7 ± 4.5 y, body mass index 23.5 ± 1.4 kg/m2). For comparative purposes, participants performed the same exercise under normoxia (FiO2 = 21%). During both exercise sessions, subjects wore a mask connected to a hypoxic gas generator while seated on a cycle ergometer. After a 4 minute rest, they pedaled for 3 minutes at 30% of their Wmax, followed by 6 minutes of recovery. Hemodynamic parameters were measured at four time points, and biological samples (blood and urine) were collected before the test and within 5 minutes of exercise completion. Samples were analyzed by 1H NMR spectroscopy. Univariate and multivariate statistical analysis of NMR datasets revealed noteworthy changes in the levels of certain metabolites following the hypoxic session: 3-hydroxybutyrate, branched-chain amino acids, citrate, lactate, phenylalanine, succinate, and tyrosine in plasma; 3-hydroxyisobutyrate, 3-hydroxyisovalerate, alanine, acetone, dimethylamine, glycine, lactate, succinate, and taurine in urine. These metabolic shifts, along with their statistically significant correlations with hemodynamic parameters, suggest an adaptive modulation of energy metabolism pathways in response to mild hypoxic stress.